Structural and functional analysis of the repressor complex in the Notch signaling pathway of Drosophila melanogaster. - Maier, D.; Kurth, P.; Schulz, A.; Russell, A.; Yuan, Z.; Gruber, K.; Kovall, R.A.; Preiss, A. (Molecular Biology of the Cell, 2011)
In metazoans, the highly conserved Notch pathway drives cellular specification. On receptor activation, the intracellular domain of Notch assembles a transcriptional activator complex that includes the DNA-binding protein CSL, a composite of human C-promoter binding factor 1, Suppressor of Hairless of Drosophila melanogaster [Su(H)], and lin-12 and Glp-1 phenotype of Caenorhabditis elegans. In the absence of ligand, CSL represses Notch target genes. However, despite the structural similarity of CSL orthologues, repression appears largely diverse between organisms. Here we analyze the Notch repressor complex in Drosophila, consisting of the fly CSL protein, Su(H), and the corepressor Hairless, which recruits general repressor proteins. We show that the C-terminal domain of Su(H) is necessary and sufficient for forming a high-affinity complex with Hairless. Mutations in Su(H) that affect interactions with Notch and Mastermind have no effect on Hairless binding. Nonetheless, we demonstrate that Notch and Hairless compete for CSL in vitro and in cell culture. In addition, we identify a site in Hairless that is crucial for binding Su(H) and subsequently show that this Hairless mutant is strongly impaired, failing to properly assemble the repressor complex in vivo. Finally, we demonstrate Hairless-mediated inhibition of Notch signaling in a cell culture assay, which hints at a potentially similar repression mechanism in mammals that might be exploited for therapeutic purposes.